IMPLIKASI PENETAPAN STATUS TERSANGKA BAGI BUPATI TERPILIH TERHADAP PEMILIHAN UMUM KEPALA DAERAH DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA - Dyah Kemala Shinta (MIH Unsoed, 2016)
Under the provisions of Article 31 paragraph (1) of Law Number 32 Year 2004 on Regional Government states that, in the head region and/or deputy regional head suspended by the President without going through Parliament because the proposal was convicted of corruption, terrorism, treason, and/or a crime against state security. The article 31 paragraph (2) of Law Number 32 Year 2004 on Regional Head if found guilty by the court decision, the Regents may be dismissed. However, the anti-corruption gives another reason that, Regent who has been declared a suspect is not good to hold office, so it is polemical. This study aimed to analyze the determination of the status of the suspect for the Regent elected as a condition. In addition it also aimed to analyze the implications of determining the status of a suspect for the Regent elected in the general election of regional heads in the constitutional system of the Republic of Indonesia, with reaserch method of yuridis normatif.Determination of the status of the suspect for the regents elected is not a limiting factor for someone to be sworn in as regent. There are two factors that hinder a person inducted into the Regional Head, which is being accused of corruption, terrorism, treason, and/or a crime against state security or convicted of treason and/or other actions that may divide the Republic of Indonesia declared by a court decision that has obtained permanent legal force. Implications for the determination of the status of a suspect in the Elected Regent regional head elections in the constitutional system of the Republic of Indonesia is divided into three implications are the implications of Ethics and Social namely the determination of the status of suspects for Elected Regent cause public distrust of the government. Political implications that gave birth to the other party the opportunity to become head of the region, as well as the legal implications of determining the status of a suspect for Regent ie not inhibit a person to induct regent elected as regent, since the Local Government Act only regulates the dismissal of the Regent, Regent's selected instead.Key Word: regent, implementation, and prinsons status